The effect of community champions on modern contraceptive knowledge, attitude and use among women of reproductive age group in rural local government areas in Lagos state - Charles-Eromosele, Titilope O.; Odeyemi, Kofoworola A. (International Journal Of Community Medicine And Public Health, 2022)
Background: The uptake of contraceptives is still low especially in rural areas in Sub-Saharan Africa. This study aimed to assess the effect of the use of community champions on knowledge, attitude and use of modern contraceptive among women of reproductive age group in rural local government areas in Lagos State. Methods: A quasi-experimental study was done among two groups. The study population were 399 women of reproductive age group per group who live in rural local government areas of Lagos state. The intervention group had community champions assigned to them while the control group did not. Multi-stage sampling method was done. It was a mixed method study. Data were collected using interviewer-administered questionnaires and from family planning registers of the health facilities in the study areas. The data were analysed using the IBM statistical products and services solutions version 23. Results: Results at post-intervention showed that there was a significant increase in the percentage of respondents with good knowledge of modern contraceptive by 22.2% (p<0.05), positive attitude towards modern contraceptives by 10.4% (p<0.05) and current use of any method of modern contraceptive by 14.3% (p<0.05) in the intervention group. While in the control group, there was no statistically significant increase in the percentage of respondents with good knowledge of modern contraceptives, positive attitude towards modern contraceptives and current use of any method of modern contraceptives. (p>0.05). Conclusions: The study concluded that the use of community champions was an effective tool for improving knowledge, attitude and use of modern contraceptives.